Tempting the best man eaudiobook - Lynn, J. (Gamble Brothers, 2013)
Madison Daniels has worshiped her brother's best friend since they were kids. Everyone thinks she and Chase Gamble would make the perfect couple, but there are two major flaws in their logic. 1) Chase has sworn off relationships of any kind and 2) after blurring the line between friends and lovers for one night four years ago, they can't stop bickering. Forced together for her brother's wedding getaway, Chase and Madison decide to call a truce for the happy couple. Except all bets are off when they're forced to shack up in a tacky '70s honeymoon suite and survive a multitude of "accidents" as the family tries to prove their "spark" can be used for more than fighting. That is, if they don't strangle each other first...